Overhead Transmission Line Maintenance in Crete and Rhodes: 2016-2020 - Pylarinos, D. (Engineering, Technology & Applied Science Research, 2021)
The Greek islands of Crete and Rhodes are equipped with isolated transmission systems that fall under the jurisdiction of the Islands Network Operation Department of HEDNO S. A., which carries out their operation and maintenance on behalf of PPC S.A. After 2016, the Transmission Line Operation and Maintenance Subsection of the Department, started to incorporate new approaches to improve the routine work of the subsection. These approaches include Unmanned Aerial Vehicle (drone) inspections, GIS/GPS software/applications and project management/issue tracking tools such as Mantis Bug Tracker (or MantisBT). This paper provides a brief review of the maintenance practices in combination with the properties and peculiarities of the specific systems, and further investigates the MantisBT records from 2016 to 2020, in order to provide a view of the routine work of transmission line maintenance through the case studies of Crete and Rhodes. It should be noted that the majority of these issues are related to the Cretan transmission system and thus, this paper also aims to provide a screenshot of the situation before the interconnection of the isolated Cretan Transmission System to the mainland system, expected to initiate in 2021.